Cypermethrin induces Sertoli cell apoptosis through mitochondrial pathway associated with calcium. Issue 4 (19th June 2021) - Wang, Heng-Xue; Zhang, Rui; Li, Zheng; Wang, Lu-Shan; Yu, Yue; Wang, Qi; Ding, Zhen; Zhang, Jin-Peng; Zhang, Mei-Rong; Xu, Li-Chun
Abstract: Cypermethrin, one kind of pyrethroid pesticides, has been shown to act as endocrine-disrupting chemicals (EDCs). The purpose of this study was to explore the roles of Sertoli cell apoptosis through mitochondrial pathway associated with calcium (Ca 2+ ) in cypermethrin-induced male reproductive toxicology. The mouse Sertoli cells TM4 were cultured with 0 μM, 10 μM, 20 μM, 40 μM and 80 μM of cypermethrin. We used flow cytometry, Fluo-4 AM, western blot and JC-1 Assay Kit to examine apoptosis, intracellular Ca 2+, expressions of mitochondrial apoptotic pathway-related proteins and mitochondrial membrane potential. We found cypermethrin increased apoptosis rate of TM4 cells significantly and with a significant increase in intracellular Ca 2+ concentration. Cypermethrin significantly decreased the protein expressions of cytosolic B-cell lymphoma-2 (Bcl-2) and mitochondrial cytochrome c (Cyt-c). The protein expressions of cytosolic Bcl-2-associated x (Bax), Cyt-c, cleaved caspase-3, calmodulin (CaM), Ca 2+ /CaM-dependent protein kinases II (CaMKII) and phosphorylated CaMKII were increased significantly in cypermethrin-exposed TM4 cells. Cypermethrin decreased mitochondrial membrane potential significantly. Then, Bcl-2 family and Ca 2+ /CaM/CaMKII pathway participate in cypermethrin-induced homeostasis. Ca 2+ overload activates mitochondrial pathway by increasing permeability of mitochondrial membrane and decreasing mitochondrial membrane potential. We suggest cypermethrin induces Sertoli cell apoptosis involving mitochondrial pathway associated with Ca 2+ regulated by Bcl-2 family and Ca 2+ /CaM/CaMKII pathway. The study provides a new insight into mechanisms involved in cypermethrin-induced male reproductive toxicology. Graphical abstract: Cypermethrin increased apoptosis rate of Sertoli cells with an increase in intracellular Ca 2+ concentration. Cypermethrin was found to decrease mitochondrial membrane potential. Cypermethrin decreased the expressions of cytosol B-cell lymphoma-2 and mitochondrial cytochrome c (Cyt-c). Cyt-c was released into cytoplasm by increasing permeability of mitochondrial membrane and decreasing mitochondrial membrane potential to activate caspase proteins including caspa-9 and casp-3, leading to apoptosis.